Oncological Outcomes of Adjuvant Radiotherapy for Partial Ureterectomy in Distal Ureteral Urothelial Carcinoma Patients - Li, Hong-zhen; Li, Xiaoying; Gao, Xian-shu; Qi, Xin; Ma, Ming-Wei; Qin, Shangbin (Frontiers in Oncology, 2021)
Purpose: We retrospectively analyzed the oncological outcomes of T3 or G3 distal ureteral urothelial carcinoma (DUUC) underwent partial ureterectomy (PU) followed by adjuvant radiotherapy (ART). Methods: From January 2008 to September 2019, clinical data from a total of 221 patients with pathologic T3 or G3 who underwent PU or RNU at our hospital were analyzed. 17 patients of them were treated with PU+ART, 72 with PU alone and 132 with radical nephroureterectomy (RNU). Clinicopathologic outcomes were evaluated. Survival was assessed using the Kaplan-Meier method. Cox regression addressed recurrence-free survival (RFS), metastasis-free survival (MFS), cancer specific survival (CSS) and overall survival (OS). Results: Median age and follow-up time were 68 (IQR 62-76) years old and 43 (IQR 28-67) months, respectively. In univariate and multivariable analyses, no lymph node metastasis(LNM) and ART were independent prognostic factors of RFS (p=0.031 and 0.016, respectively). ART significantly improved 5-year RFS compared with the PU alone, (67.6% vs. 39.5%, HR: 2.431，95%CI 1.210-4.883，p=0.039). There was no statistical difference in 5-year RFS between PU+ART and RNU groups (67.6% vs. 64.4%, HR=1.113，95%CI 0.457-2.712，p=0.821). Compared with PU alone or RNU, PU+ART demonstrated no statistical difference in 5-year MFS (PU+ART 73.2%, PU 57.2%, RNU69.4%), CSS (70.7%, 55.1%, 76.6%, respectively), and OS (70.7%, 54.1%, 69.2%, respectively). Conclusions: For distal ureteral urothelial carcinoma patients with T3 or G3, adjuvant radiotherapy could significantly improve recurrence-free survival compared with partial ureterectomy alone. There was no significant difference between survival outcomes of PU+ART and radical nephroureterectomy. Keywords: Urothelial carcinoma, Partial ureterectomy, Radical nephroureterectomy, Adjuvant radiotherapy, Recurrence-free survival (RFS)